1994
DOI: 10.1016/0014-5793(94)00752-7
|View full text |Cite
|
Sign up to set email alerts
|

Presence of protein phosphatase type 1 and its involvement in temperature‐dependent flagellar movement of fowl spermatozoa

Abstract: Even in the presence of ATP, the motility of demembranated fowl spermatozoa was negligible at the avian body temperature of 40°C. Motility could be restored by the addition of calyculin A, okadaic acid, specific inhibitors of phosphatase type I (PPI) and PP-ZA, and inhibitor I or inhibitor 2, which are specific inhibitors of protein phosphatase type I (PPl). Demembranated spermatozoa, stimulated by caiyculin A or okadaic acid, lost their motility following the addition of I mM CaCI,, but this was restored grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Calyculin A has a potency similar to that of okadaic acid as an inhibitor of PP2A, but is 10-to 100-fold more effective as an inhibitor of PP1 (Ishihara et al 1989). The present study showed that the motility of fowl spermatozoa at 40 8C was stimulated by calyculin A and was effective at 10-to 100-fold lower concentrations of calyculin A than those of okadaic acid, confirming earlier results (Ashizawa et al 1994b). In contrast, the acrosome reaction in the presence of IPVL was stimulated in the same dose-dependent manner by both 10-1000 nmol/l okadaic acid and calyculin A.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Calyculin A has a potency similar to that of okadaic acid as an inhibitor of PP2A, but is 10-to 100-fold more effective as an inhibitor of PP1 (Ishihara et al 1989). The present study showed that the motility of fowl spermatozoa at 40 8C was stimulated by calyculin A and was effective at 10-to 100-fold lower concentrations of calyculin A than those of okadaic acid, confirming earlier results (Ashizawa et al 1994b). In contrast, the acrosome reaction in the presence of IPVL was stimulated in the same dose-dependent manner by both 10-1000 nmol/l okadaic acid and calyculin A.…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that PP1 and/or PP2A are involved in the regulation of acrosome reaction but that only PP1 is involved in the regulation of motility of fowl spermatozoa. It seems that both phosphatases are present in fowl spermatozoa, since immunoblotting of sperm extract using an antibody to PP1a revealed a major cross-reacting protein of 36-37 kDa which corresponds to the molecular weight of the catalytic subunit of PP1 a (Ashizawa et al 1994b), and in this study, a protein of approximately 36 kDa was recognised by anti-PP2A antibody which corresponds to the molecular weight of the catalytic subunit of PP2A. Therefore, in conclusion, different or different combinations of protein phosphatases are involved in the regulation of the acrosome reaction of fowl spermatozoa than those involved in the regulation of fowl sperm motility, i.e., protein dephosphorylation by PP2B and PP1 and/or PP2A in the former, and PP1 alone in the latter case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory serine/threonine protein phosphatases, such as myosin light chain phosphatase, are classified into four main enzymes: type 1 (PP1), type 2A (PP2A), type 2B (PP2B) and type 2C (PP2C); myosin light chain phosphatase activity in smooth muscle is classified as PP1 (Cohen 1989). On the other hand, PP1 appears to be dominant in the temperature-dependent inhibition of flagellar movement of fowl spermatozoa at body temperatures of 40 8C, since the motility of demembranated fowl spermatozoa at 40 8C was stimulated by the addition of calyculin A or okadaic acid (specific inhibitors of PP1 and PP2A), and inhibitors 1 and 2 (small heat-stable proteins which inhibit PP1 activity) (Ashizawa et al 1994b). In addition, the motility of demembranated fowl spermatozoa at 30 8C decreased markedly following the addition of recombinant PP1 supplemented with Mn 2þ (Ashizawa et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that the control factors of phosphatase to sperm motility might be confined to the axoneme [Habermacher and Sale 1996]. This is supported by the observation of the gain of motility after the addition of protein phosphatase 1 inhibitors to demembraned fowl spermatozoa [Ashizawa et al 1994].…”
Section: Mechanisms Of Spermatozoa Flagellar Motility Controlmentioning
confidence: 97%